Asymmetry of Radial and Symmetry of Tangential Neuronal Migration Pathways in Developing Human Fetal Brains - Miyazaki, Yuta; Song, Jae W.; Takahashi, Emi (Frontiers in Neuroanatomy, 2016)
The radial and tangential neural migration pathways are two major neuronal migration streams in humans that are critical during corticogenesis. Corticogenesis is a complex process of neuronal proliferation that is followed by neuronal migration and the formation of axonal connections. Existing histological assessments of these two neuronal migration pathways have limitations inherent to microscopic studies and are confined to small anatomic regions of interest (ROIs). Thus, little evidence is available about their three-dimensional (3-D) fiber pathways and development throughout the entire brain. In this study, we imaged and analyzed radial and tangential migration pathways in the whole human brain using high-angular resolution diffusion MR imaging (HARDI) tractography. We imaged ten fixed, postmortem fetal (17 gestational weeks (GW), 18 GW, 19 GW, three 20 GW, three 21 GW and 22 GW) and eight in vivo newborn (two 30 GW, 34 GW, 35 GW and four 40 GW) brains with no neurological/pathological conditions. We statistically compared the volume of the left and right radial and tangential migration pathways, and the volume of the radial migration pathways of the anterior and posterior regions of the brain. In specimens 22 GW or younger, the volume of radial migration pathways of the left hemisphere was significantly larger than that of the right hemisphere. The volume of posterior radial migration pathways was also larger when compared to the anterior pathways in specimens 22 GW or younger. In contrast, no significant differences were observed in the radial migration pathways of brains older than 22 GW. Moreover, our study did not identify any significant differences in volumetric laterality in the tangential migration pathways. These results suggest that these two neuronal migration pathways develop and regress differently, and radial neuronal migration varies regionally based on hemispheric and anterior-posterior laterality, potentially explaining regional differences in the amount of excitatory neurons that migrate along the radial scaffold.